Egg Tray Daun Salam (Eugenia polyantha) - Isna Bekti Pratiwi; Muryoto Muryoto; Rizki Amalia (Sanitasi: Jurnal Kesehatan Lingkungan, 2017)
Chicken egg is one of foods that highly nutritious and has good taste and inexpensive, as well as can be processed into various food products. However, the characteristic of chicken eggs is their quality can be easily degraded and perishable because the shelf-life is relatively short. This research, in general was aimed to know the effect of egg tray consisted of Eugenia polyantha leaves towards the length of shelf life of chicken eggs which were washed and unwashed. Specifically, the purpose of the research was to know the effect of 0 %, 20 % and 40 % compositon ratio of the leaves, by conducting a true experiment with post test only control group design. As the control was egg tray which is found in markets. In each egg tray, 10 washed eggs and 10 beforehand unwashed eggs were placed and kept at room temperature. The length of eggs’ shelflife were observed in twenty-seven days, and was based on the change of their condition. The data were analysed by using one way Anova at ? 0,05; and the results indicate that egg tray with 40 % Eugenis polyantha leaves is the most effective for prolonging the shelf-life of washed chicken eggs. The obtained value of mean difference and p-value were 14.00000 and < 0,001, respectively.